Mfap4: a promising target for enhanced liver regeneration and chronic liver disease treatment - Iakovleva, Viktoriia; Wuestefeld, Anna; Ong, Agnes Bee Leng; Gao, Rong; Kaya, Neslihan Arife; Lee, May Yin; Zhai, Weiwei; Tam, Wai Leong; Dan, Yock Young; Wuestefeld, Torsten (npj Regenerative medicine, 2023)
The liver has a remarkable regenerative capacity. Nevertheless, under chronic liver-damaging conditions, this capacity becomes exhausted, allowing the accumulation of fibrotic tissue and leading to end-stage liver disease. Enhancing the endogenous regenerative capacity by targeting regeneration breaks is an innovative therapeutic approach. We set up an in vivo functional genetic screen to identify such regeneration breaks. As the top hit, we identified Microfibril associated protein 4 (Mfap4). Knockdown of Mfap4 in hepatocytes enhances cell proliferation, accelerates liver regeneration, and attenuates chronic liver disease by reducing liver fibrosis. Targeting Mfap4 modulates several liver regeneration-related pathways including mTOR. Our research opens the way to siRNA-based therapeutics to enhance hepatocyte-based liver regeneration.